CAST IRON WITH VERMICULAR GRAPHITE IS A CONSTRUCTIVE MATERIAL OF MODEM MACHINE-BUILDING - S. P. Korolev; E. V. Panfilov (Литьë и металлургия, 2006)
It is shown that using of cast iron with vermicular graphite in national economy proves its prospects as a construction material dues to technological effectiveness and economy.